Uniform decay rates for solutions to a structural acoustics model with nonlinear dissipation - Avalos, George; Lasiecka, Irena (Zielona Góra: Uniwersytet Zielonogórski)
In this work, the asymptotic behavior of solutions to a coupled hyperbolic/parabolic-like system is investigated. It is shown that with both components of the equation being subjected to nonlinear damping (boundary damping for the wave component, interior for the beam), a global uniform stability is attained for all (weak) solutions.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka